Factors Affecting Pupils’ Learning in the New Normal at Saint Michael College of Caraga - Janine T Arranz; Aires B Daligdig; Shiela Marie P Abao; Felix E Arcilla Jr (RIRAI Publisher, 2022)
The world is facing serious issues due to the COVID-19 pandemic influencing people's economic, social, and lifestyle. The issue badly affects the educational system and institutions because nationwide closure stops classroom activities. The study aimed to investigate the factors affecting pupils’ learning in the new normal at Saint Michael College of Caraga. The study utilized the descriptive quantitative research method. The researchers used survey questionnaires via google forms with the 58 pupils in Grades 3 to 6, who were the study's respondents using the purposive sampling method. Based on the findings, there is a moderate extent of the factors affecting pupils’ learning in the new normal. This means that the pupils learning in the new normal is moderately affected by six factors: the perceived ease of use of technology, perceived usefulness of technology, faculty capacity of the school, course content in e-learning, course design in e-learning, and learner’s characteristics. It was recommended that the school administration continue supporting and providing the Learning Management System to the students for better learning. The pupils' perceived usefulness of technology helps them in the new normal learning; therefore, the teachers are encouraged to use videos, audios, and instant messaging to contact and provide feedback to the pupils. Moreover, teachers must monitor pupils' learning since the online classroom is new. The teacher’s reinforcement is significantly important to secure the learning for pupils online learning to be successful.